2017
DOI: 10.1590/1980-5373-mr-2017-0173
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Microstructure, Texture, and Formability Between 11CrTi and 11CrTi+Nb ASTM 409 Ferritic Stainless Steel

Abstract: Stabilization of ferritic stainless steel ASTM 409, for use in automobile exhaust systems, is increasingly in demand, due to higher exhaust gas temperatures. Ti is one of the most commonly used elements. However, high concentrations cause problems during steel casting; however, stabilization with Ti and Nb represents a good alternative. The present study aims to investigate the effect of adding Nb on the microstructure, texture, and forming properties of Ti-stabilized ferritic steels. The results demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Several studies have investigated the texture evolution of FSSs during forming processes using different techniques such as X-ray diffraction (XRD) [8][9][10][11][12], electron backscatter diffraction (EBSD), and scanning electron microscopy (SEM), [8][9][10][11][12][13][14][15][16][17][18] and only a small number of studies employed transmission electron microscopy (TEM) [13,19]. Some of these studies focused on cold-worked FSSs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the texture evolution of FSSs during forming processes using different techniques such as X-ray diffraction (XRD) [8][9][10][11][12], electron backscatter diffraction (EBSD), and scanning electron microscopy (SEM), [8][9][10][11][12][13][14][15][16][17][18] and only a small number of studies employed transmission electron microscopy (TEM) [13,19]. Some of these studies focused on cold-worked FSSs.…”
Section: Introductionmentioning
confidence: 99%
“…Others studied the texture evolution to understand the ridging process that FSSs may experience during forming, like Ma et al [16], who found that this defect is avoided by preventing the formation of coarse bands and grains with the {001} component in 430 and 430 LR. However, most of these studies focused on the most popular standard grade of FSSs, AISI 430 [11,16], while others explored the texture evolution of modified grades with higher contents of Ti and Nb, which have improved corrosion resistance and weldability [8][9][10][13][14][15][17][18][19]. None of these works studied the influence of the slight modification of the typical alloy elements of AISI 430 standard composition, such as Si, Mn, Cr, C, and N. Moreover, there is a lack of comprehensive and comparative analysis of the texture evolution of different grades of FSSs after deep drawing and its relation to their formability and mechanical performance.…”
Section: Introductionmentioning
confidence: 99%